Pengaruh Produk Domestik Regional Bruto (PDRB) terhadap Tingkat Kemiskinan Kota Medan - Reni Ria Armayani Hasibuan; Anggi Kartika; Firdha Aigha Suwito; Lismaini Agustin (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study has the benefit of analyzing the effect of regional gross domestic product on poverty in the city of Medan in 2010-2020. The research method used is a quantitative method with reference to a descriptive approach. The data used is time series data on economic growth and poverty at the Central Statistics Agency (BPS) of Medan City in 2010-2020. Data collection techniques used are journals, book documentation, and previous reports. The technique of analyzing the data uses simple linear regression analysis which is carried out to determine whether the model used is free from deviations from the classical assumption test. The equations obtained from the simple linear regression analysis test Y = 24576.325 – 0.365X and have the understanding that the GRDP variable (X) has a significant effect on Poverty (Y). Obtained a value of R2 (R square) of 0.556 with the understanding that the independent variable, namely GRDP, affects the variable of the poverty level in Medan City by 55.6%. Meanwhile, the remaining 44.4% are influenced by different independent variables and are not included in this study. For this reason, it can be concluded that when GRDP increases, it will have an impact on decreasing the value of Poverty in Medan City, and vice versa. Keywords: Gross Regional Domestic Product; Poverty; Medan city